Tarkovsky screens Hemingway: Andrei Tarkovsky's first student film, The Killers (1956). (4th May 2019) - Luca, Raymond De
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article discusses Andrei Tarkovsky's first student film The Killers (1956), based on Ernest Hemingway's 'The Killers'. It explores the significance of the choice of a piece of foreign literature, a text by Hemingway, in 1956 for a student of VGIK. The article further studies the collaboration with Aleksandr Gordon and Maria Beiku, and draws out the approaches that make visible the influence of Italian neo-realism and connect this film to Tarkovsky's later work.